PENDAMPINGAN PEMBUATAN BADAN HUKUM BUMDes HASIL BERKAH MOTEKAR DESA NAGRAK - Tuti Herawati; Mulyadi Mulyadi (Universitas Pahlawan Tuanku Tambusai, 2022)
Nagrak Village, Ciater District, located in Subang Regency has a BUMDes with the name Hasil Berkah Motekar which has been established since 2017. There is a Job Creation Law which explains that now BUMDes can run a business and/or public service company and form a legal entity business unit. The BUMDes does not yet have a legal entity, because the management of the BUMDes is constrained by technical problems in its management. During this period of service, assistance was provided in creating a business entity for the BUMDes of Nagrak Village. The activity was carried out in 3 stages, among them: Observation, discussion with the manager and registering BUMDes to the Ministry of Law and Human Rights. In this period of service, the author can contribute to BUMDes Results Berkah in obtaining a new Legal Entity which means it has the same position as business entities in general and hopes to be able to facilitate village partnerships, introduce regional potential, accelerate village economic development and success. National Sustainable Development Goals (SDGs). Keywords: Business Entities, BUMDes, Employment Creation Act